Вивчення процесів формування підповерхневих тріщин у ромбічній сортовій заготовці при виробництві в умовах металургійного мікро-заводу - Смірнов, О.М.; Ухін, В.Є.; Верзілов, О.П.; Семенко, А.Ю.; Гойда, Д.І.; Куліш, Ю.Ю. (Physico-technological Institute of Metals and Alloys, 2023)
The development of technological schemes of steel production in recent years is characterized by a decrease in the volume of steel produced within individual enterprises while improving the quality of products. In turn, the production of high-quality and high-quality steel grades today is becoming more justified in the conditions of modern metallurgical micro-mills than in the conditions of mini-mills and large shops. This trend is justified by the ability to produce quality products in small batches. The high quality of the cast billet means the provision of high conditions in terms of geometric configuration and the absence of surface and subsurface cracks. One of the causes of metal breakthroughs is the formation of a slag film or gap between the work-piece and the surface of the mold, which prevents efficient heat dissipation and leads to local compaction of the rigid frame and metal breakthrough under the action of ferrostatic pressure. Another origin of this kind of emergency situation is considered to be the softening of the crust due to the appearance of internal cracks directed from the center of the ingot to the surface in the formation of the rhombicity of the work-piece profile. However, in practice, there are cases when in a rhombic workpiece, the breakthrough of the metal under the mold causes cracks that do not go from the center of the workpiece to the surface, but, conversely, from surface to center. The purpose of this work is to study and identify the processes and phenomena that accompany the formation of cracks and are the cause of metal breakthrough and directed from the surface of the ingot to its center in a rhombic billet. This paper presents research and analysis of processes and phenomena that accompany the formation of cracks in the steel billet. The reason for the breakthrough of metal of a diamond-shaped grade billet, which is concentrated in the area between the surface of the metal ingot and its center, is considered. It is established that the appearance of surface cracks during casting of a varietal billet on continuous casting machines (CCM) or semi-continuous casting machines (SCCM), caused by transverse decrease and increase of rhombicity of the billet in the range from 1–2 mm. It is confirmed that such processes in turn occur due to the mismatch of the size of the sleeve profile in height to the parameters of shrink-age of the hard crust of the metal.